МАХМУД ҚОШҒАРИЙНИНГ «ДЕВОНУ ЛУҒАТИТ ТУРК» ЛЕКСИКАСИНИНГ ЎЗБЕК ШЕВАЛАРИ БИЛАН МУШТАРАКЛИГИ - Ибрагимов, Ю.М. (SCIENCE and SOCIETY, 2021)
The article deals with the description of the lexical layer ”Devonu” by Makhmud Kashgariyin in the comparative–historical aspect with the Southerm-Aral Uzbek dialects. The author ties comparatively the singormanic variants of the lexical layer and distinguishes polysemantic, synonymous and antonymous peculiarities. The reason of changing the forms and meaning have proven on the basis of empirical evidence.